X-raying Circumstellar Material around Young Stars. Issue Volume 10:Issue S314(2015) (November 2015) - Schneider, P. C.; Günther, H. M.
Abstract: Young stars are surrounded by copious amounts of circumstellar material. Its composition, in particular its gas-to-dust ratio, is an important parameter. However, measuring this ratio is challenging, because gas mass estimates are often model dependent. X-ray absorption is sensitive to the gas along the line-of-sight while optical/near-IR extinction depends on the dust. Therefore, the absorber's gas-to-dust ratio is directly given by the ratio between X-ray and optical/near-IR extinction. We present three systems where we used X-ray and optical/near-IR data to constrain the gas-to-dust ratio of circumstellar material; from a dust rich debris disk to gaseous protoplanetary disks.